Invasive hemodynamics and cardiac biomarkers to predict outcomes after percutaneous edge-to-edge mitral valve repair in patients with severe heart failure - Kreußer, Michael; Geis, Nicolas; Berlin, Nicolas; Greiner, Sebastian; Pleger, Sven Torsten; Katus, Hugo; Raake, Philip (Clinical research in cardiology, 2019)
BackgroundPercutaneous mitral valve repair (PMVR) via MitraClip implantation is a therapeutic option for high-risk or non-surgical candidates with severe mitral regurgitation (MR) and advanced stages of heart failure (HF). However, these patients have a high mortality despite PMVR, and predictors for outcomes are not well established. Here, we evaluated invasive hemodynamics, echocardiography parameters, and biomarkers to predict outcomes after PMVR in severe HF patients.MethodsPatients with reduced ejection fraction (EF) and severe and moderate-to-severe MR undergoing PMVR at our centre between September 2009 and January 2016 were analysed retrospectively. Inclusion criteria were: left ventricular EF < 45%, preoperative right heart catheterization, successful MitraClip deployment (“technical success”), and follow-up for at least 1 year after the procedure. Data from preoperative right heart catheterization, echocardiography, and biomarkers were assessed. Primary endpoint was all-cause mortality at 1 year after PMVR. We performed univariate and multivariate Cox regression analyses and generated a risk score to predict outcomes.ResultsOf 174 patients with PMVR and severe HF, 79.9% had functional MR. Mean EF was 25% (17.2; 30.7) and advanced New York Heart Association functional class was prevalent (class II: 13%; class III: 70%; and class IV: 17%). The cumulative incidences of all-cause death were 6.9% and 17.8% at 30 days and 1 year, respectively. In the Cox multivariate model, high-sensitive troponin T [hsTnT; hazard ratio (HR) 1.01; confidence interval (CI) 1.01-1.02; p < 0.0001] and mixed venous O2-saturation (HR 0.92; CI 0.89-0.96; p < 0.0001) were found to significantly and independently predict outcomes. A simple risk score including these two parameters was sufficient to discriminate between low- and high-risk patients (HR 7.22; CI 3.4-15.5; p < 0.001).ConclusionIn a cohort of patients with severe HF undergoing PMVR, patients with elevated hsTnT and reduced mixed venous O2-saturation carried the worst prognosis. A simple risk score including these two parameters may improve patient selection and outcomes after PMVR.
Published online: 6 September 2018
Gesehen am 21.05.2019